1990
DOI: 10.1007/bf01966449
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous osteo-arthritis of the knee-joint in C57BL mice receiving chronic oral treatment with NSAID's or prednisone

Abstract: In a statistically planned study based on quantitative radiography, treatment for 25-26 weeks with the 2 NSAIDs, diclofenac sodium, or indomethacin (both 0.5 and 1.5 mg/kg p.o. daily), or prednisone (6 mg/kg p.o.) had no influence on the progression of spontaneous osteo-arthritis of the knee-joint of the C57BL mouse, by comparison with placebo-treated controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Other investigators have previously used image analysis of radiographs to measure the severity of experimental osteoarthritis (27)(28)(29). In these studies, changes in the joint space width, the area and density of the menisci, and the area and density of the femoral and tibia1 epiphyses were measured by image analysis as an index of the severity of spontaneously occurring disease in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have previously used image analysis of radiographs to measure the severity of experimental osteoarthritis (27)(28)(29). In these studies, changes in the joint space width, the area and density of the menisci, and the area and density of the femoral and tibia1 epiphyses were measured by image analysis as an index of the severity of spontaneously occurring disease in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be noted that histopathological diagnosis is concerned with only one parameter and radiographic diagnosis with two that are independent of each other, but both change in the course of the disease. Thus, as was to be expected, in a consecutive study quantitative radiographic diagnosis demonstrated the occurrence of meniscus enlargement and narrowing of the joint space as manifestations of the spontaneous progression of the disease [12]. The advantages of quantitative radiographic diagnosis over histopathological diagnosis are also that it is non-invasive and takes much less time.…”
Section: Discussionmentioning
confidence: 92%
“…Spontaneous degenerative knee joint disease has been observed in the C57BL/6 strain. Thus, with age (after 15.5 months) enlargement of menisci as well as narrowing of the joint space has been observed 26,27 . Histological evidence of cartilage destruction as early as 6e8 months of age has been reported, albeit with slow progression, whereby 80% of mice examined showed signs at 16e18 months, and almost all mice showed signs at 2 years 28 .…”
Section: Discussionmentioning
confidence: 95%